CASE STUDY: HIJAMAH THERAPY FOR LOW BACK PAIN - Khasanah, Uswatun (Prodi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, UIN Syarif Hidayatullah Jakarta, 2024)
Background: Chronic pain was the common reason for visiting health professionals and neuropathic pain was mostly associated with low back pain. Hijamah has the potential benefit for low back pain therapy. This study investigated the effects of Asaabil Hijamah Techniques for reducing pain in patients with low back pain. Method: Case study was applied as a study approach. There was 3 female patients, mean age 48,67 age years old with low back pain observed. Pre and post pain assessment were completed using the PQRST pain assessment, while the pain level assessed using a numeric pain scale. Results: The results indicated that Assabil Hijamah Techniques effectively reduced the pain scale, with an average reduction of 1.3 points in the patient study group. Conclusion: This study recommends further study about understanding and potential benefit long-term effects of Hijamah.